Clustering of hydrochloric acid on the surface of C60/C70 fullerite and its composites with nanosilica: Bildung von Chlorwasserstoff‐Oberflächenclustern an C60/C70 Fulleriten und deren Kompositen mit Nanosilikaten. Issue 2 (29th January 2016) - Turov, V. V.; Prylutskyy, Y. I.; Krupskaya, T. V.; Schur, D. V.; Evstigneev, M. P.; Kartel, M. T.; Ritter, U.
Abstract : The formation of cluster structures on the surface of fullerite C60 /C70 and its composites with nanosilica (A‐300, AM1‐300 and A‐300+AM1‐300) with hydrochloric acid in a hydrophobic environment was studied by means of low‐temperature 1 H NMR spectroscopy. It was established that the surface of fullerite crystals can separate hydrochloric acid solution into its components, and in the environment of weakly polar organic solvent, CDCl3, the substantial fraction of water exists in a weakly associated state. It was shown that the composite nanosystems made of fullerite and silica (A‐300, AM1‐300 and their 1 : 1 mixture), the adsorption of hydrochloric acid predominantly occurs on a silica part of the composite. Addition of dimethyl sulfoxide to the medium results in formation of several types of clusters on the surface, which include water molecules, hydrogen chloride and dimethyl sulfoxide, wherein less associated forms are localized predominantly on the surface of the fullerite (their number is maximal for the combined (A‐300 + AM1‐300)/C60 composites). Therefore the features of the cluster structures and their site of localization in the volume of the solid phase can be controlled by varying the content of the composite nanosystem.